Finance Act 2021 Notes: Section 112: repeal of carbon emissions tax - Pirlot, A (Sweet and Maxwell, 2021)
Notes provisions of the Finance Act 2021 s.112, repealing measures in the Finance Act 2019 and Finance Act 2020 which imposed a carbon emissions tax to allow transition from the EU Emissions Trading Scheme (ETS) pending the implementation of a UK ETS.